2013
DOI: 10.1002/cam4.135
|View full text |Cite
|
Sign up to set email alerts
|

Oncologists’ attitudes toward KRAS testing: a multisite study

Abstract: Recent discoveries promise increasingly to help oncologists individually tailor anticancer therapy to their patients’ molecular tumor characteristics. One such promising molecular diagnostic is Kirsten ras (KRAS) tumor mutation testing for metastatic colorectal cancer (mCRC) patients. In the current study, we examined how and why physicians adopt KRAS testing and how they subsequently utilize the information when discussing treatment strategies with patients. We conducted 34 semi-structured in-person or teleph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In the physician survey, we have shown that by 2012, the percentage of participating physicians adopting tumor KRAS testing was nearly 100% in Europe. Previous physician surveys in 2010 following published guidance recommending the adoption of KRAS testing prior to EGFR-targeted treatment [ 18 , 19 ] found that the range of adoption varied widely (20–100%) across countries [ 20 22 ]. In Europe in 2010, physicians used clinical judgment when deciding whether or not to test mCRC KRAS status prior to treatment with EGFR-targeted therapies, with 73% of participating physicians testing mCRC KRAS status prior to prescribing EGFR-targeted therapies [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the physician survey, we have shown that by 2012, the percentage of participating physicians adopting tumor KRAS testing was nearly 100% in Europe. Previous physician surveys in 2010 following published guidance recommending the adoption of KRAS testing prior to EGFR-targeted treatment [ 18 , 19 ] found that the range of adoption varied widely (20–100%) across countries [ 20 22 ]. In Europe in 2010, physicians used clinical judgment when deciding whether or not to test mCRC KRAS status prior to treatment with EGFR-targeted therapies, with 73% of participating physicians testing mCRC KRAS status prior to prescribing EGFR-targeted therapies [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous physician surveys have found that in 2010, when guidelines first recommended testing for KRAS status [ 18 , 19 ], the adoption of KRAS testing prior to treating patients with EGFR inhibitors varied widely [ 20 22 ]. In 2010, 73% (326/448) of participating physicians in Europe reported undertaking appropriate KRAS testing when mCRC was diagnosed, compared with 63% (160/256) in Latin America and 20% (28/139) in Asia [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). As adoption of NGS methods in tumour screening increases, however, there will be a need to revise research on patients' attitudes and experiences.With somatic tumour screening being embraced by oncologists to fill an informational need when making treatment decisions(Gray, Hicks-Courant, Cronin, Rollins, & Weeks, 2014;Harris et al, 2013; This may influence test interest(Meiser, Storey, Quinn, Rahman, & Andrews, 2016), asGray et al (2012) found that cancer patients were less willing to undergo germline cancer risk testing with the potential of yielding incidental information (81%), compared to somatic testing to guide treatment selection (96%).…”
mentioning
confidence: 99%
“…Physicians who care for cancer patients are challenged by the need to learn about new developments in the field and the demand to apply these new tools in patient care [ 1 ]. Realizing the potential benefits of molecular diagnostic testing in cancer care will require high levels of physician receptivity and readiness to use such tests routinely [ 2 , 3 ]. To date, however, limited research has reported on physician receptivity to and use of molecular diagnostic testing in cancer care [ 4 ].…”
Section: Introductionmentioning
confidence: 99%